Stability of micronutrients and phytochemicals of grapefruit jam as affected by the obtention process. (April 2016) - Igual, M; García-Martínez, E; Camacho, MM; Martínez-Navarrete, N
Fruits are widely revered for their micronutrient properties. They serve as a primary source of vitamins and minerals as well as of natural phytonutrients with antioxidant properties. Jam constitutes an interesting way to preserve fruit. Traditionally, this product is obtained by intense heat treatment that may cause irreversible loss of these bioactive compounds responsible for the health-related properties of fruits. In this work, different grapefruit jams obtained by conventional, osmotic dehydration (OD) without thermal treatment and/or microwave (MW) techniques were compared in terms of their vitamin, organic acid and phytochemical content and their stability through three months of storage. If compared with heating, osmotic treatments lead to a greater loss of organic acids and vitamin C during both processing and storage. MW treatments permit jam to be obtained which has a similar nutritional and functional value than that obtained when using a conventional heating method, but in a much shorter time.